The Role of Guidance Counselors in Junior High Schools in Addressing Drug Abuse Among Students - Varisa Nuralya; Mardi Lestari; Azam Arifyadi; Nur Eka Wahyuningsih Ariyadi (MASI Mandiri Edukasi, 2025)
This study aims to describe the role of guidance and counseling teachers in preventing drug abuse among students. The sample in this study consisted of 5 participants, namely three students and two guidance and counseling teachers, using an interview instrument as the data collection instrument. The data obtained was then processed and analyzed using descriptive qualitative methods. The results of the study show that guidance and counseling teachers play an important role in preventive efforts through routine socialization activities about the dangers of drugs, instilling an attitude of rejection of peer pressure, and providing individual and group counseling services. Guidance and counseling teachers also conduct early detection through behavioral observation, personal approaches to students who show indications of drug abuse, and collaborate with the National Narcotics Agency (BNN) and parents in the case handling process. In addition, students involved in drug abuse were given follow-up assistance in the form of routine check-ups at the BNN according to the severity of their condition. The findings of the study reveal that collaborative efforts between guidance counselors, schools, the BNN, and families play a significant role in creating a safe school environment and supporting the prevention of drug abuse. This study confirms that the role of guidance counsellors extends beyond problem handling to include character development, awareness-raising, and the formation of healthy behaviours in students.